THE RUSSIAN LANGUAGE AS AN INSTRUMENT OF RUSSIA'S POSITIVE IMAGE FORMATION - Pervova, G.M.; Maslova, M.V. (Tambov University Review Series Humanities, 2016)
The importance of civil-patriotic education of students that is realized during the formation of a positive attitude to the mother tongue is discussed. The appeal to the concept of “love for the mother tongue” in the federal state educational standards of general education (in the requirements for personal, meta-subject and subject results of learning educational programs, in the list of characteristics that make up the “Graduate’s portrait”) is analyzed. Examples of precedent texts glorifying Russian language (statements by M.V. Lomonosov, G.R. Derzhavin, I.A. Bunin, A.I. Kuprin, K.G. Paustovsky), and provocative texts (articles by Yu.V. Rozhdestvensky, B. Meltsa, M.N. Epshteyna, D.L. Bykov) are given. The importance for a combination of rhetorical and grammatical approaches in Russian language teaching is proved. Detailed description of the content and structure of the workbook, developed in order to foster positive attitudes of pupils to their native language and form the national value orientations (country, morality, conscience, dignity, honesty, love, kindness, honor) in their minds, is given. It is proved the importance of learning within the subject field “Philology”, the state's history and language, different language areas. Attempt to determine the nature of love to the mother tongue basing on article by S. Averintsev “Panegyric for Philology”, which reveals the originality of “intellectual love” to the language, is made.